Frost protection : - Snyder, Richard L. (Food and Agirculture Organization of the United Nations, 2005)
When air temperatures fall below 0º C, sensitive crops can be injured, with significant effects on production. In this book, the distribution, economies, history, physical and biological aspects of frost damage are presented and discussed, together with methods of protection. This book contains a broad range of information from basic to complex: however, it was mainly written to help growers to better understand freeze protection and to develop strategies to combat crop losses due to freezing.